Recent changes in the fire regime across the North American boreal region-Spatial and temporal patterns of burning across Canada and Alaska - Kasischke, Eric S.; Turetsky, Merritt R. (Geophysical research letters, 2006)
We used historic records from 1959–99 to explore fire regime characteristics at ecozone scales across the entire North American boreal region (NABR). Shifts in the NABR fire regime between the 1960s/70s and the 1980s/90s were characterized by a doubling of annual burned area and more than a doubling of the frequency of larger fire years because of more large fire events (>1,000 km2). The proportion of total burned area from human‐ignited fires decreased over this same time period, while the proportion of burning during the early and late‐ growing‐seasons increased. Trends in increased burned area were consistent across the NABR ecozones, though the western ecozones experienced greater increases in larger fire years compared to the eastern ecozones. Seasonal patterns of burning differed among ecozones. Along with the climate warming, changes in the fire regime characteristics may be an important driver of future ecosystem processes in the NABR.